The effect of the "Prestige" oil spill on the plankton of the N-NW Spanish coast - Varela, Manuel; Álvarez-Salgado, Xosé Antón (Marine Pollution Bulletin, 2006)
15 páginas, 3 tablas, 8 figuras.-- Manuel Varela . et al. Chlorophyll, primary production, zooplankton biomass and the species composition of phytoplankton and zooplankton were studied in 2003, after the Prestige shipwreck. The information obtained was compared to previous data series available for the area affected by the spill. A large data series on plankton variables for the N–NW Spanish coast existed, and therefore a realistic evaluation of the effects by comparison with the range of natural variability could be carried out. We emphasized the evaluation of impact during the spring bloom, the first important biological event after the spill. Some minor changes were observed occasionally, but they did not show any clear pattern and were more related to the natural variability of the ecosystem than to effect of the spill. Plankton community structure did not undergo any changes. Only a few species were more abundant during spring 2003 than in previous years. No significant changes were detected in the planktonic community during productive periods, such as the spring bloom and the summer blooms related to intrusions of East North Atlantic Central Waters. The lack of evidence of the effects of the spill on planktonic communities is discussed in terms of the characteristics of the fuel, the high dynamics of the water masses, the biological mechanisms through which the fuel from the surface waters is transferred to the sea floor and, particularly, the influence of the natural variability by means of large and meso-scale hydrographic processes in the area under study. At the present time it is not possible to determine any minor effects the spill may have had on the plankton owing to the great variability of the planktonic cycles and the short-term impact of the oil from the Prestige on the pelagic system. C. Garcı´a-Soto would like to acknowledge a Ramo´n y Cajal contract and financial support from the project VEM 2004-08613. This work was partially funded by the Natural Environment Research Council core ...